Effect of Processing Conditions on Heat Seal Strength for Peelable Heat Sealing of Multilayered Polyethylene Films with Different Sealant Layers. Issue 9 (2nd September 2017) - Iwasaki, Toshiharu; Takarada, Wataru; Kikutani, Takeshi
ABSTRACT: The effect of heat sealing temperature on peelable heat seal strength (HSS) before and after the sterilization, often used industrially, was investigated for one of either polyethylene (PE) multilayered films with various inner sealant layers consisting of two high density PEs (HDPEs), a linear low density PE (LLDPE) or low density PE (LDPE). To attain similar HSS, heat sealing at a temperature close to the melting peak temperature (Tm-p) was needed only in the case of LDPE. Heat sealing behavior at higher temperatures, to attain higher HSS, was also investigated for HDPE and LDPE. High HSS, as well as suppressed reduction of HSS after the sterilization, was achieved for HDPE at a heat sealing temperature well below its Tm-p. An Increase of HSS with the increase of dwell time was also observed. On the other hand, for LDPE, high HSS and its stability after the sterilization were achieved only when the heat sealing temperature was increased to the value equivalent to its Tm-p. Improvement of the processing conditions for the shortening of the processing period was also investigated. For HDPE, higher sealing bar temperature was needed to gain similar HSS when the dwell time of the heat sealing was shortened from 4 to 2 s, whereas the attained maximum temperature at the interface was found to be similar. The characteristics of the heat sealed portion, judged from the relation between HSSs before and after the sterilization, were not affected by the dwell time of heat sealing, indicating that the shortening of the processing time by appropriate raising of the sealing bar temperature is possible.